PkM Edukasi Organisasi Tim Tanggap Darurat di Area Kerja pada Karyawan PT. Sarana Tirta Alamindo - Ridwan Usman; Elfitria Wiratmani; Galuh Krisna Dewanti (Abdimas Universal, 2022)
An emergency is an unexpected difficult situation that requires immediate treatment to prevent accidents/fatalities. The work environment has the potential for emergencies such as fires and earthquakes. According to risk identification data, the work environment area must be prepared to face disasters by preparing resources. Support infrastructure facilities and human resources. Support infrastructure facilities and human resources. Prevention efforts to minimize risk are by planning a disaster emergency response system. Emergency response unit is a work unit specially formed to deal with emergency situations in the workplace. Emergency response teams work quickly to deal with all disaster events quickly, precisely, and accurately and to reduce the incidence of casualties and losses due to disaster events. Implementation of community service activities for employees of PT. Sarana Tirta Alamindo provides participants with an understanding of emergency response so that they are able to plan emergency response preparedness in the work area. The results of the emergency response socialization activity in the work area, employees understand the importance of being ready for emergency response, through training and discussion all must be familiar and able to apply in their work area emergency response conditions and the importance of support from company leaders to form an emergency response team that works and is directly responsible for handling the situation. work area emergency.